Antinociceptive effect of tebanicline for various noxious stimuli-induced behaviours in mice. (18th January 2017) - Hayashi, Takafumi; Katsuyama, Soh; Orito, Tohru; Suzuki, Tsuneyoshi; Sakurada, Shinobu
Highlights: Tebanicline (ABT-594; 0.05–1.6 μmol/kg, s.c.) had dose-dependent analgesic effects in the formalin, hot-plate and tail-pressure tests. The antinociceptive effect of tebanicline was not shown in the tail-flick assay (dose > 1.6 μmol/kg, s.c.). Tebanicline might not only act on a nicotinic acetylcholine receptor, but might also affect the opioid receptor indirectly. Abstract: Tebanicline (ABT-594), an analogue of epibatidine, exhibits potent antinociceptive effects and high affinity for the nicotinic acetylcholine receptor in the central nervous system. We assessed whether tebanicline exerts an effect on various noxious stimuli and mediates the nicotine receptor or opioid receptor through stimulation. The antinociceptive effects of tebanicline were determined by noxious chemical, thermal and mechanical stimuli-induced behaviours in mice. Tebanicline had dose-dependent analgesic effects in formalin, hot-plate and tail-pressure tests. By contrast, the antinociceptive effect of tebanicline was not demonstrated in the tail-flick assay. Pre-treatment with mecamylamine, a nicotinic acetylcholine receptor antagonist, blocked the effects of tebanicline in formalin, tail-pressure and hot-plate tests. Moreover, pre-treatment with naloxone, an opioid receptor antagonist, only partially inhibited the effects of tebanicline in formalin and tail-pressure tests. Tebanicline produced antinociception in persistent chemical (formalin), acute thermal (hot-plate, but not tail-flick) and mechanical (tail-pressure) pain states. Moreover, tebanicline stimulated the nicotinic acetylcholine receptor and opioid receptor.